The Effect of Tangram Media Assited Think Pair Share Model on Calculation Ability Area and Circumference Plane Geometry - Andromeda, Bravura; Mardiana, Tria; Wijayanto, Sukma (Prosiding University Research Colloquium, 2021)
This research aims to determine the effect of the Think Pair Share model assisted bytangram media on the ability to calculate the area and perimeter of flat shapes in fourthgrade students of primary school in Purworejo. This research is a type of pre-experimentalresearch with one group pretest-posttest design. Sampling was selected by saturatedsampling. The samples taken were 19 students. The method of data collection is done byusing a description test. The validity test uses the product moment formula, while thereliability test uses the Cronbach alpha formula which produces a reliability index of 0.945.Data analysis used parametric statistical techniques, namely the Paired Sample T-Testwith the help of the SPSS for Windows version 26.00 program. The results of the analysisof the Data Test of Two Dependent Samples carried out using the Paired Sample T-Testwith a t count > t table, which is 17.006 > 2.093 with an Asymp value. Sig. (2-tailed) 0.000< 0.05. Based on the results of the analysis and discussion, there are difference in theaverage score of the ability to calculate the area and perimeter of plane geometry, namelythe pretest average of 48.1, while the posttest average is 76.8. This shows that there is aninfluence of the TPS model assisted by Tangram media on the ability to calculate the areaand perimeter of plane geometry in fourth grade students of primary school Academic Year2020/2021.